2022
DOI: 10.3390/hydrology9010012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Climate and Land Use/Land Cover Change on Water Availability in an Inland Valley Catchment in Burkina Faso

Abstract: Water scarcity for smallholder farming in West Africa has led to the shift of cultivation from uplands to inland valleys. This study investigates the impacts of climate and land use/land cover (LULC) change on water resources in an intensively instrumented inland valley catchment in Southwestern Burkina Faso. An ensemble of five regional climate models (RCMs) and two climate scenarios (RCP 4.5 and RCP 8.5) was utilized to drive a physically-based hydrological model WaSiM after calibration and validation. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…In the African highlands of this agricultural watershed, however, high and intense soil erosion is one of the most distinctive characteristics. Studies highlight that high soil erosion from agricultural watersheds causes crop production losses [ [22] , [23] , [24] , [25] , [26] ]; (Thakuriah, 2023), sedimentation of reservoirs, resulting in severe economic losses to irrigation and hydroelectric projects [ [27] , [28] , [29] ]. As a result, a study confirmed that Africa lost 40% of agricultural productivity and covered an average of one-fifth of dam storage volumes with silt [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the African highlands of this agricultural watershed, however, high and intense soil erosion is one of the most distinctive characteristics. Studies highlight that high soil erosion from agricultural watersheds causes crop production losses [ [22] , [23] , [24] , [25] , [26] ]; (Thakuriah, 2023), sedimentation of reservoirs, resulting in severe economic losses to irrigation and hydroelectric projects [ [27] , [28] , [29] ]. As a result, a study confirmed that Africa lost 40% of agricultural productivity and covered an average of one-fifth of dam storage volumes with silt [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Gbohoui et al [2021] showed that for varying nested watersheds scale, the control of environmental conditions (i.e., land use) is dependent on the size of the watershed. In contrast for example, in southwestern Burkina Faso, Idrissou et al [2022] projected to the 2050 horizon an increase in surface runoff (12% to 95%) and also a decrease (24% to 44%), primarily driven by land use changes in both cases.…”
Section: On the Contributions Of Climate And Land Use Changes To Surf...mentioning
confidence: 99%
“…Modeling tools have become useful to simulate the combined effects of climate-land interactions but also help to establish mechanisms leading to various environmental outcomes including biodiversity (Schulte to Bühne et al, 2021;Srinivasan and Wilcove, 2021), population (Molotoks et al, 2021), pathogens (Casazza et al, 2020), and food security impact of elevated CO 2 (J. , just to mention a few. Modeling tools have dominated climate-land related research due to their ability to model complex interactions and better represent environmental concerns such as stream ow and hydrological predictions, pollutant loading, water balance, and water quality (Achugbu et al, 2021;Alamdari et al, 2022;Boone et al, 2016;Cao and Dan, 2021;Chilukoti & Xue, 2021;Gabiri et al, 2020;Hung et al, 2020;Idrissou et al, 2022;Jain et al, 2021;Nyatuame et al, 2020;Ross and Randhir, 2022;Selwood et al, 2014;Srinivasan and Wilcove, 2021;Sylla et al, 2016;Tirupathi and Shashidhar, 2020;Tu, 2009), amongst others.…”
Section: Introductionmentioning
confidence: 99%